HUBUNGAN NITRIC OXIDE DAN ENDOTELIN-1 PADA WANITA DIABETES MELLITUS TIPE-2 DENGAN HIPERTENSI - , DITA RIA SELVYANA; , dr. R. Bowo Pramono, Sp.PD-KEMD, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Prevalence of hypertension in DM was found twice higher than in non- DM patient. Hypertension in DM increases the risk of coronary heart disease, peripheral arterial disease, cerebrovascular accident and renal failure. Several studies on DM with hypertension indicate that endothelial dysfunction is closely associated with increased endothelin-1. A variety of metabolic pathways can lead to activation of endothelin in diabetes include activation of protein kinase C (PKC), activation of polyol pathway, non-enzymatic glycation, changes in expression of growth factors and oxidative stress resulting in decreased nitric oxide (NO) which then led to increasing expression of endothelin-1. NO is a vasoactive enzyme produced by endothelial cells which have effects vasodilatation and antiproliferation on vascular smooth muscle cells. Several previous studies showed that elevated blood glucose levels can lead to decreased levels of NO plasma, leading to increased levels of endothelin-1, which in turn lead to endothelial dysfunction and hypertension. Aim. To analyze the relationship between nitric oxide and endothelin-1 levels in women with type 2 diabetes and hypertension. Methods. This study used cross sectional design. The subjects were type 2 diabetes with hypertension patients in Endocrine and Metabolic clinic Dr. Sardjito hospital, Yogyakarta, age between 40 to 60 years and visit between Juli 2010 until Desember 2010 that met inclusion and exclusion criteria. Blood samples were taken for NO and endothelin-1 levels examination with ELISA. The correlation between these two variables was analyzed with Spearman correlation test. Results. There are 40 subjects type 2 diabetes with hypertension. Plasma level of NO was 0.6107 ± 0.268184 µM and plasma level of endothelin-1 was 17.8614010 9.78231877 ± pg/ml. Spearman correlation analysis of the results obtained a negative correlation between plasma NO concentration and plasma endothelin-1 concentration, with (r)= -0.070, and not statistically significant with P value = 0669. Conclusion. There is no correlation between plasma levels of nitric oxide and endothelin-1 in women with type 2 diabetes and hypertension.